LAMP1 targeting of the large T antigen of Merkel cell polyomavirus results in potent CD4 T cell responses and tumor inhibition - Buchta Rosean, Claire; Leyder, Erica C.; Hamilton, Jeneice; Carter, Joseph J.; Galloway, Denise A.; Koelle, David M.; Nghiem, Paul; Heiland, Teri (Frontiers in Immunology, 2023)
Most cases of Merkel cell carcinoma (MCC), a rare and highly aggressive type of neuroendocrine skin cancer, are associated with Merkel cell polyomavirus (MCPyV) infection. MCPyV integrates into the host genome, resulting in expression of oncoproteins including a truncated form of the viral large T antigen (LT) in infected cells. These oncoproteins are an attractive target for a therapeutic cancer vaccine.We designed a cancer vaccine that promotes potent, antigen-specific CD4 T cell responses to MCPyV-LT. To activate antigen-specific CD4 T cells in vivo, we utilized our nucleic acid platform, UNITE TM (UNiversal Intracellular Targeted Expression), which fuses a tumor-associated antigen with lysosomalassociated membrane protein 1 (LAMP1). This lysosomal targeting technology results in enhanced antigen presentation and potent antigen-specific T cell responses. LT S220A , encoding a mutated form of MCPyV-LT that diminishes its pro-oncogenic properties, was introduced into the UNITE TM platform.Vaccination with LT S220A -UNITE TM DNA vaccine (ITI-3000) induced antigen-specific CD4 T cell responses and a strong humoral response that were sufficient to delay tumor growth of a B16F10 melanoma line expressing LT S220A . This effect was dependent on the CD4 T cells' ability to produce IFNγ. Moreover, ITI-3000 induced a favorable tumor microenvironment (TME), including a Th1-type cytokines profile and significantly enhanced numbers of CD4 and CD8 T cells as well as NK and NKT 2 This is a provisional file, not the final typeset article cells. Additionally, ITI-3000 synergized with an α-PD-1 immune checkpoint inhibitor to further slow tumor growth and enhance survival.These findings strongly suggest that in pre-clinical studies, DNA vaccination with ITI-3000, using the UNITE TM platform, enhances CD4 T cell responses to MCPyV-LT that result in significant anti-tumor immune responses. These data support the initiation of a first-in-human (FIH) Phase 1 open-label study to evaluate the safety, tolerability, and immunogenicity of ITI-3000 in patients with polyomaviruspositive MCC (NCT05422781).